Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas XI MIA SMAN 7 PADANG - YULINAR . (Departemen Matematika, 2019)
Mathematical problem solving skill is one of the goals of mathematics learning that must be achieved by students through the process of learning mathematics. But in fact learning activities in schools are not optimal in facilitating students to improve mathematical problem solving skills. One effort to overcome this problem is to apply the Problem Based Learning (PBL) model. The purpose of this study is to describe whether the mathematical problem solving skills of students who learn by using the PBL model are better than students who learn with direct learning model. This type of research is quasi-experimental with the Randomized Control Group Only Design research design. Based on the results of data analysis, it was concluded that the mathematical problem solving skills of students who learn to use the PBL model are better than students who learn with direct learning model in class XI SMAN 7 Padang. Keywords – Mathematical Problem Solving, Problem Based Learning Model, Direct Learning Model